Wildfire influences on stream water geochemistry in a boreal catchment - Nordblad, Fredrik (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2011)
Forest wildfires are important for the structure and functioning of boreal ecosystems including biogeochemical processes. During the last decades, natural forest fires have been successfully suppressed in Fennoscandia. Therefore, our knowledge on the biogeochemical effects of forest fires is limited. In August 2006, a 1500 ha forest fire occurred near Bodträskfors, northern Sweden. The intensity of the fire varied among vegetation types. Especially in areas dominated by pine forest of the lichen type, vegetation and the humus layer were burnt to a large extent whereas the impact in moist-wet forest patches was less pronounced. Burning and subsequent leaching of plant remainders was expected to affect local surface waters. The main objectives with this thesis were to: 1) investigate the behavior of water quality parameters (pH, conductivity) and dissolved major elements including TOC (Total Organic Carbon) due to leaching of burnt plant remainders and, 2) measure the dissolved concentration and isotopic composition of boron as a potential tracer of forest fires. The project was performed in 2007 – 2009 in a creek draining the burnt area. A creek in a neighboring catchment not affected by the fire was sampled as a reference. Both catchments are characterized by the same type of bedrock and soil cover.The results indicate that leaching of the burnt plant remainders was mainly contributing P, K, Ca and Mg to creek water run-off. This is consistent with the naturally high concentrations of these elements in plant tissue. Na was not leached to any greater extent. Compared to the reference creek, burnt creek concentrations of N were slightly higher and slightly lower for TOC. The pH was ~ 0.5 units lower in the burnt creek during all years of measurement. Conductivity was higher in the burnt creek in 2007 but had decreased to the levels of the reference creek in 2009. Conductivity appeared to be controlled by Ca and Mg concentration as the temporal variations of these parameters/elements were closely correlated. During ...